Provision and Collection of Safety Evidence: A Systematic Literature Review - Maria de Oliveira, Lilandra; Martins, Luiz Eduardo Galvão; Marques, Johnny Cardoso (Revista de Informática Teórica e Aplicada, 2023)
Safety-Critical Systems (SCS) are becoming more and more present in modern societies’ daily lives, increasing people’s dependence on them. Current SCS are firmly based on computational technology; possible failures in the operation of these systems can lead to accidents and endanger human life, as well as damage the environment and property. SCS are present in many areas such as avionics, automotive systems, industrial plants (chemical, oil & gas, and nuclear), medical devices, railroad control, defense, and aerospace systems. Companies that develop SCS must present evidence of their safety to obtain certification and authorization. This paper presents a Systematic Literature Review (SLR) to investigate processes, tools, and techniques for collecting and managing safety evidence in SCS. The authors conducted this SLR according to the guidelines proposed by Kitchenham and Charters. The SLR comprises seven (7) research questions that investigate essential aspects of collecting and managing safety evidence. The primary studies analyzed in this SLR were selected based on a search string applied into four data sources: ACM, IEEE Xplore, SpringerLink, and ScienceDirect. Data extraction considered (fifty-one) 51 primary studies. The authors identified eleven (11) different approaches covering processes, tools, and techniques for collecting and managing safety evidence. Despite other SLR works conducted about safety evidence, none of them focused on the details related to safety evidence collection. We found that very few approaches focused specifically on the process of collecting safety evidence.